Hippocampal metabotropic glutamate receptor long‐term depression in health and disease: focus on mitogen‐activated protein kinase pathways. (4th May 2016) - Sanderson, Thomas M.; Hogg, Ellen L.; Collingridge, Graham L.; Corrêa, Sonia A. L.
Abstract: Group I metabotropic glutamate receptor (mGluR) dependent long‐term depression (LTD) is a major form of synaptic plasticity underlying learning and memory. The molecular mechanisms involved in mGluR‐LTD have been investigated intensively for the last two decades. In this 60th anniversary special issue article, we review the recent advances in determining the mechanisms that regulate the induction, transduction and expression of mGluR‐LTD in the hippocampus, with a focus on the mitogen‐activated protein kinase (MAPK) pathways. In particular we discuss the requirement of p38 MAPK and extracellular signal‐regulated kinase 1/2 (ERK 1/2) activation. The recent advances in understanding the signaling cascades regulating mGluR‐LTD are then related to the cognitive impairments observed in neurological disorders, such as fragile X syndrome and Alzheimer's disease. mGluR‐LTD is a form of synaptic plasticity that impacts on memory formation. In the hippocampus mitogen‐activated protein kinases (MAPKs) have been found to be important in mGluR‐LTD. In this 60th anniversary special issue article, we review the independent and complementary roles of two classes of MAPK, p38 and ERK1/2 and link this to the aberrant mGluR‐LTD that has an important role in diseases. This article is part of the 60th Anniversary special issue . Abstract : mGluR‐LTD is a form of synaptic plasticity that impacts on memory formation. In the hippocampus mitogen‐activated protein kinases (MAPKs) have been found to be important in mGluR‐LTD. In this 60th anniversary special issue article, we review the independent and complementary roles of two classes of MAPK, p38 and ERK1/2 and link this to the aberrant mGluR‐LTD that has an important role in diseases. This article is part of the 60th Anniversary special issue .